Equitable and effective clinical guidance development and dissemination: trauma aims to lead the way - Deborah M Stein; Elliott R Haut; Eileen M Bulger; Vanessa P Ho; Andres M Rubiano; Ashley Farley; Lacey N LaGrone; Danielle J Wilson; Maria Michaels; Meghan B Lane-Fall; Michael A Person; Linda Reinhart (Trauma Surgery & Acute Care Open)
Thirty-four per cent of deaths among Americans aged 1–46 are due to injury, and many of these deaths could be prevented if all hospitals performed as well as the highest-performing hospitals. The Institute of Medicine and the National Academies of Science, Engineering and Medicine have called for learning health systems, with emphasis on clinical practice guidelines (CPGs) as a means of limiting preventable deaths. Reduction in mortality has been demonstrated when evidence-based trauma CPGs are adhered to; however, guidelines are variably updated, redundant, absent, inaccessible, or perceived as irrelevant. Ultimately, these barriers result in poor guideline implementation and preventable patient deaths. This multidisciplinary group of injury providers, clinical guidance developers and end users, public health and health policy experts and implementation scientists propose key areas for consideration in the definition of an ideal future state for clinical guidance development and dissemination. Suggestions include (1): professional societies collaborate rather than compete for guideline development.(2) Design primary clinical research for implementation, and where relevant, with guideline development in mind.(3) Select clinical topics for guideline development through systematic prioritization, with an emphasis on patient-centered outcomes.(4) Develop guideline authorship groups with a focus on transparency, equity of opportunity and diversity of representation.(5) Establish a plan for regular review and updating and provide the date the guideline was last updated for transparency.(6) Integrate options for adapting the guideline to local resources and needs at the time of development.(7) Make guidelines available on a platform that allows for open feedback and utilization tracking.(8) Improve discoverability of guidelines.(9) Optimize user-experience with a focus on inclusion of bedside-ready, mobile-friendly infographics, tables or algorithms when feasible.(10) Use open access and open licenses.(11) Disseminate clinical guidance via comprehensive and equitable communication channels. Guidelines are key to improve patient outcomes. The proposed focus to ensure trauma guidelines are equitably and effectively developed and disseminated globally.